(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
A set of twoquestionnaires (appendix B & C) was addressed to each of the branches,which financed above borrowers. One was for the particular borrower selectedabove to verify the information, which was received from the borrower and alsofor making corrections using credit records in the concerned branch. The otherwas general to collect the relevant data of the branch regarding advances made,recovery, supervision and branch managers’ views on quality lending andsuggestions on SAA. A number of districtdevelopment agencies of state govt. sponsor cases to bank branches forfinancing and providing subsidy to the loaners so assisted. SAA envisagesco-ordination of the working of these agencies on one hand and bankers on theother hand. So views of project director of DRDA were also obtained throughquestionnaire (appendix-E). Questions pertainedto adequacy of credit, proper utilization of credit etc. The schemes of theseagencies are implemented by their block/village level workers who remain inconstant touch with the bank borrowers. Hence views of some of such workerswere also obtained through questionnaire (appendix F) covering aspects likeinfrastructure, adequacy of credit, utilization of credit, supervision by banketc.